Avaliação de linfócitos T reguladores em pacientes convalescentes da Covid-19 - Palmeira, Pedro Henrique de Sousa (2022)
Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2), the causative agent of Coronavirus Disease 2019 (COVID-19), causes a range of clinical symptoms that can lead to death. Although several studies have demonstrated the pivotal role of the host immune system in the development of distinct clinical profiles, many questions still remain. In the present study, comparative analyses in Regulatory T cells (Treg) of the volunteers not previously infected with SARS-CoV-2 (HC) and volunteers who recovered from mild (Mild Recovered) and severe (Severe Recovered) COVID-19 were performed. Peripheral Blood Mononuclear Cells (PBMC) from enrolled volunteers were stimulated with SARS-CoV-2 related peptides (Pool Spike CoV-2 and Pool CoV-2) or Staphylococcal enterotoxin B (SEB). Using a multicolor flow cytometric assay were reported higher levels of Treg frequency and expression of IL-10, IL-17, perforin, granzyme B, PD-1, and CD39+CD73+ coexpression by studied lymphocytes in Mild Recovered compared to Severe Recovered and/or HC groups in some SARS-CoV-2 related stimulus. Moreover, Mild Recovered unstimulated PBMCs also presented more frequency of Tregs and expression of IL-10 and granzyme B than HC, suggesting long-term immunomodulation after disease resolution. Compared to Pool CoV-2 stimuli, Pool Spike CoV-2 reduced the IL-10 while improving PD-1 expression by Tregs from Mild Recovered volunteers. Curiously, Pool Spike CoV-2 elicited a decrease in Tregs IL-17+ frequency in Severe Recovered. In HC, the expression of LAP and cytotoxic granules coexpression by Treg were higher in Pool CoV-2 stimulated samples suggesting an immunological cross-reactivity. In the present study, comparative analyses of the immunological data between Mild Recovered volunteers who experienced or did not experience some symptoms during the acute phase of COVID-19 were also performed. The main results showed that Pool Spike CoV-2 stimulus elicited a decreased pattern of Tregs IL-10+ and Tregs CTLA-4+ frequency in PBMC from volunteers who did not develop some symptoms. Moreover, higher levels of perforin and perforin+granzyme B+ coexpression by regulatory T cells were found in Mild Recovered volunteers who experienced dyspnea. Finally, were observed differential expressions of the ectonucleotidases CD39 and CD73 in Tregs between Mild Recovered volunteers that experienced musculoskeletal pain. Collectively, this study suggests that changes in immunosuppressive tools of Tregs could influence the development of a distinct COVID-19 clinical profile. Considering the comparative data of the Mild Recovered group, this work revealed a possible modulation at the Treg level that could help in the establishment of mild disease, thus having a great potential to contribute to the scientific efforts in understanding COVID-19 immunity.